Multibiosignal chaotic encryption scheme based on spread spectrum and global diffusion process for e-health. (September 2022) - Murillo-Escobar, M.A.; Cruz-Hernández, C.; Cardoza-Avendaño, L.; Murillo-Escobar, D.; López-Gutiérrez, R.M.
Abstract: E-health provides several remote health services highly convenient for patients. Nevertheless, inherent security risks are present in e-health such as data privacy since insecure communication channels are used to transmit data between patients and physicians or to cloud medical data storage. Nowadays, medical body area network provides a solution to continuous health monitoring with real-time updates of multibiosignal records in multiuser communication schemes for monitoring and early detection of medical conditions or diseases. In this paper, we propose to use chaos-based sequence direct spread spectrum technology and chaos-based cryptography to provide data privacy, high security and efficiency in monitoring multibiosignals in multiuser networks for e-health applications. First, each plain biosignal is modulated with sequence direct spread spectrum by using the chaotic Hénon map. Then, all modulated biosignals are summed to produce the modulated cryptogram. The modulated cryptogram is finally encrypted by using global diffusion process with the chaotic Hénon map to increase security by reducing the high autocorrelation of the modulated cryptogram. The experimental results are presented in a simulated multiuser scenario with 4 users (or patients) and 2 specialists (neurologist and cardiologist), with 12 biosignals acquired from database on the Internet, such as electroencephalograms, electromyograms, blood pressure signals, and electrocardiograms. A comprehensive security study is presented to show the high security, the high speed encryption, and the high noise interference robustness. According with the results, the proposed method can be used for secure multibiosignal monitoring in multiuser networks for e-health applications with high efficiency and security. Graphical abstract: Highlights: Encryption algorithm based on spread spectrum with chaotic diffusion is proposed. Multibiosignals are encrypted together in a multiuser network for e-health. One round of global chaotic diffusion process increases considerably the security. Four patients transmit twelve biosignals securely to two specialists. High security and efficiency are achieved in simulation results.